Situation Report: Romania, 14 November 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Journal Rejects East-Bloc Assimilation / by Anneli Maier The State of Emergency and the Militarization of the Power Industry / by Paul Gafton The Black Market Flourishes / by Dan Ionescu Controversial Poet Back on the Literary Scene / by Crisula Stefanescu The Size of the Hungarian and German Minorities / by Paul Gafton